Vulnerable Atherosclerotic Carotid Plaque Evaluation by Ultrasound, Computed Tomography Angiography, and Magnetic Resonance Imaging: An Overview. Issue 3 (August 2014) - Naim, Cyrille; Douziech, Maxime; Therasse, Éric; Robillard, Pierre; Giroux, Marie-France; Arsenault, Frederic; Cloutier, Guy; Soulez, Gilles
Ischemic syndromes associated with carotid atherosclerotic disease are often related to plaque rupture. The benefit of endarterectomy for high-grade carotid stenosis in symptomatic patients has been established. However, in asymptomatic patients, the benefit of endarterectomy remains equivocal. Current research seeks to risk stratify asymptomatic patients by characterizing vulnerable, rupture-prone atherosclerotic plaques. Plaque composition, biology, and biomechanics are studied by noninvasive imaging techniques such as magnetic resonance imaging, computed tomography, ultrasound, and ultrasound elastography. These techniques are at a developmental stage and have yet to be used in clinical practice. This review will describe noninvasive techniques in ultrasound, magnetic resonance imaging, and computed tomography imaging modalities used to characterize atherosclerotic plaque, and will discuss their potential clinical applications, benefits, and drawbacks.